Using Flex (Field Works Language Explorer) program for Megrelian texts - Tsulaia, Nino; Skhulukhia, Tamuna ("Intercultural Dialogues" Transactions, 2023)
Modern technologies are actively used in the field of humanities. It became essential to apply them in linguistics as well. In the wake of technological development, it became possible to create language databases, which have been contributing to the representation and preservation of languages in a diachronic and synchronic way. It became topical to create language corpora, which makes it possible to preserve the language in the same form as it functions at a given moment. Language corpora are especially timely for unwritten, endangered languages found all over the world and also in Georgia. One of them is Megrelian, an unwritten language, which can be said to be at the edge of extinction. Our future goal is related to creating a Megrelian language corpus, which will include earlier and contemporary fieldwork data gathered from various districts of Samegrelo. The creation of the corpus will make it possible to study and investigate Megrelian broadly; to explore its sociocultural and linguistic (phonological, morphological) tendencies. With the passage of time, the grammatical issues of languages are changing. Thus, it is important to capture and solve them. It is appropriate to use the corpus for the lexicographic purposes as well. Within the framework of the project, together with the compiling of the corpus, our goal is to create an electronic and printed dictionary. Defined tasks are performed and the fieldwork data is analyzed using the program FLEx (Fieldworks Language Explorer). The main stages of the entire working process are: obtaining and recording the aimed fieldwork data; describing the data and providing phonological annotations; compiling the data in the program and providing morphological analysis. The corpus will contribute to the protection of the language under analysis. This corpus will be of significant help to linguists and researchers.